MODEL LITERASI MEDIA PADA ANAK DALAM MENCEGAH KONFLIK SOSIAL - Alip Kunandar (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2014)
This study is the first step to find a model of media literacy related to the prevention of social conflicts. Focus Group Discussion (FGD) used to find patterns of media consumption on children’s television, where to watch, and accompaniment patterns while watching television. FGD also used to find some examples of media content that has the potential to trigger social conflict. The results showed the existence of irregularities in terms of time children watch television, as well as place. Children are also often accompanied while watching, so they does not have someone to discuss the content they watch on television. Moreover, in the context of the conflict, many potential social conflicts derived from the child’s television, especially in the form of words (diction) wich sensitive to trigger social conflict. The results of the study, indicate the need for Protectionist Media Literacy Models, which aims to protect children from unsuitable and useful content, even potentially lead to social conflict.